Indoor soundscapes at home during the COVID-19 lockdown in London – Part I: Associations between the perception of the acoustic environment, occupantś activity and well-being. (1st December 2021) - Torresin, Simone; Albatici, Rossano; Aletta, Francesco; Babich, Francesco; Oberman, Tin; Stawinoga, Agnieszka Elzbieta; Kang, Jian
Abstract: Since the outbreak of the COVID-19 pandemic, as a result of the adoption of worldwide lockdown measures, the home environment has become the place where all the daily activities are taking place for many people. In these changed social and acoustical contexts, we wanted to evaluate the perception of the indoor acoustic environment in relation to traditional and new activities performed at home, i.e., relaxation, and working from home (WFH). Taking London as a case study, the present paper presents the results of an online survey administered to 464 home workers in January 2021. The survey utilized a previously developed model for the assessment of indoor soundscapes to describe the affective responses to the acoustic environments in a perceptual space defined by comfort (i.e. how comfortable or annoying the environment was judged) and content (i.e., how saturated the environment is with events and sounds) dimensions. A mixed-method approach was adopted to reinforce result validity by triangulating data from questionnaires and spontaneous descriptions given by participants. In this first part of the study, the main objectives were: (1) evaluating differences in soundscape evaluation, in terms of comfort and content dimensions, based on the activity performed at home, (2) identifying appropriate conditions for WFH and relaxation, and (3) investigating associations between psychological well-being and indoor soundscapes. The results showed that the environments were perceived as more comfortable and slightly fuller of content when rated in relation to relaxation than for WFH, thus suggesting a stricter evaluation of the acoustic environment in the latter case. As regards the second objective, spaces that were more appropriate for relaxation had high comfort, whereas spaces appropriate for WFH resulted more private and under control, i.e. with high comfort and low content scores. Lastly, better psychological well-being was associated with more comfortable soundscapes, both for WFH (rs  = 0.346, p < .0005), and relaxation (rs  = 0.353, p < .0005), and with lower content while WFH (rs  = −0.133, p = .004). The discussion points out the need of considering the implications of changed working patterns to rethink the design of soundscapes in residential buildings, also in relation to potential well-being outcomes that will be further investigated in the Part II of the study.